Influence of cultivation techniques on dry matter partitioning, nitrogen distribution pattern and yield of super hybrid rice Liangyoupeijiu (Bangladesh Rice Journal, 2023)
Liangyoupeijiu was grown under different crop cultivation techniques viz: conventional tillage and transplanting (CTTP), no tillage and transplanting (NTTP), conventional tillage and direct seeding (CTDS) and no- tillage and direct seeding (NTDS) during 2011 and 2012. Results showed that, CTTP had higher leaf dry weight than NTTP. Maximum leaf dry weight reduced in direct seeded than transplanted rice. Shoot dry weight reduced by 6% both in transplanted and direct seeded rice from heading to 12 days after heading (DAH) in both the years. No tillage and transplanting had higher export percentage of dry matter and transport percentage of dry matter among the cultivation techniques in both the years. At heading, leaf nitrogen concentration (%) and nitrogen uptake (g m-2) were higher in transplanted than direct seeded rice and significantly higher nitrogen uptake was observed under conventional tillage and transplanting in both the years. The physiological nitrogen use efficiency was higher in no-tillage than conventional tillage in both the years. Total nitrogen (kg ha-1) uptake was higher in conventional tillage than no tillage either in transplanted or in direct seeded rice and was higher under conventional tillage and transplanting among the cultivation techniques in both the years. Grain yield was closely associated with uptake of total nitrogen at heading. Although, direct seeded rice had more than 23% higher panicle number than transplanted rice but conventional tillage and transplanting produced higher grain yield due to higher uptake of nitrogen by grain at maturity and bigger sink size.Bangladesh Rice J. 26 (2): 51-62, 2022